Everyone has a role to play: academic integrity, professional development and third space - Loretta Goff (Journal of Learning Development in Higher Education)
Academic integrity is fundamental to many aspects of higher education, including ensuring the validity of degrees, the quality of academic work and the development of academic literacies. Everyone has a role to play in this area but it also requires dedicated academic integrity roles to lead this work. Often, individuals directly employed in this field are positioned as third-space professionals with responsibilities for policy, procedure and/or training, education, and pedagogical support. When approaching academic integrity from the educational and pedagogical perspective, it can be a challenge to reach everyone (from this third space) with best practice guidance on fostering academic integrity across an institution. This article presents a case study of a micro-credential course, ‘Fostering Academic Integrity in Learning and Teaching’. This course was developed in collaboration with academic and professional staff and is offered as a professional development opportunity to all who support student learning. The course, and its impact, not only demonstrate the success of third-space collaboration but also the importance of third-space expertise (with time dedicated to specific research areas, like academic integrity) for informing the practice of academic colleagues at an institution.